ASSOCIATION RULE METHOD FOR INFORMATION SYSTEM EPIDEMIC DENGUE MAPPING BASED ASSOCIATION OF RISK FACTORS IN PALEMBANG - Ermatita Ermatita; Suci Destriatania (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Endemic diseases dangerous such as dengue fever must be handling seriously  for the risk minimize by the disease. Dengue Hemorrhagic Fever (DHF) is  disease  has not been found vaccine or cure is powerful. It is  necessary  treatment to prevent the occurrence of dengue fever, especially when it came to the incidence of dengue fever endemic in certain areas by doing Epidemiologist dengue fever. Epidemiology is identification of risk factors for DHF to find level of area  risk. Risk factors of hemorrhagic fever endemic must be identified  to prevent the occurrence of dengue fever. Identifying risk factors and  risk factors association  can  potential increase  the occurrence of dengue fever. This study developed  mapping information system Dengue epidemic through Association rule method of data mining. The information generated in the map of epidemic DHF level based association of potential risk factors that cause hemorrhagic fever endemic. Analysis with the Association Rule to determine level of  DHF epidemic area based data reporting system. KEY WORDS: information system mapping, data mining, Association Rule, endemic, Dengue Hemorrhagic Fever (DHF).